Taking advantages of intramolecular hydrogen bonding to prepare mechanically robust and catalyst-free vitrimer. (1st December 2020) - Wang, Shuaipeng; Teng, Na; Dai, Jinyue; Liu, Jingkai; Cao, Lijun; Zhao, Weiwei; Liu, Xiaoqing
Abstract: Fabrication of mechanically robust and catalyst-free vitrimers is of great importance, but often challenging. Herein, a facile strategy to achieve this goal by incorporation of intramolecular hydrogen bonds into the dynamic covalent network is demonstrated. Specifically, glycidyl methacrylate (GMA) is reacted with bio-renewable malic acid (MA) to generate a UV-curable resin containing ester linkages. On account of the proximity between the α -carbonyl and β -hydroxyl groups in MA, six-membered-ring intramolecular hydrogen bonds ( O-H⋯O=C ) are formed in the cross-linked network. This formation of intramolecular hydrogen bonds endows the network with enhanced and outstanding mechanical properties, showing tensile strength and Young's modulus of 117.7 MPa and 3.66 GPa, respectively. Meanwhile, the network is able to efficiently alter its topology without external catalyst through transesterifications reactions at high temperatures. We attributed this phenomenon to the presence of intramolecular hydrogen bonds which make the α -carbonyl carbon more positive and be more reactive towards nucleophilic attack, and thus facilitate the transesterification reaction. This work suggests a promising route to achieve catalyst-free thermosets with superior mechanical performances, good self-healing ability and reprocessability. Graphical abstract: Image 1 Highlights: Fabricating mechanically robust and catalyst-free vitrimer by incorporating intramolecular H-bonds. The vitrimer shows tensile strength of 117.7 MPa and Young's modulus of 3.6 GPa. Intramolecular H-bonds showed an accelerated effect on transesterification. A UV-curable monomer is synthesized to achieve the vitrimer material.